A compact underactuated gripper with two fingers and a retractable suction cup - Courchesne, Julien; Cardou, Philippe; Rachide Onadja, Palamanga Abdoul (Frontiers in Robotics and AI, 2023)
Modern industrial applications of robotics such as small-series production and automated warehousing require versatile grippers, i.e., grippers that can pick up the widest possible variety of objects. These objects must often be grasped or placed inside a container, which limits the size of the gripper. In this article, we propose to combine the two most popular gripper technologies in order to maximise versatility: finger grippers and suction-cup (vacuum) grippers. Many researchers and a few companies have followed this same idea in the past, but their gripper designs are often overly complex or too bulky to pick up objects inside containers. Here, we develop a gripper where the suction cup is lodged inside the palm of a two-finger robotic hand. The suction cup is mounted on a retractile rod that can extend to pick up objects inside containers without interference from the two fingers. A single actuator drives both the finger and sliding-rod motions so as to minimise the gripper complexity. The opening and closing sequence of the gripper is achieved by using a planetary gear train as transmission between the actuator, the fingers and the suction cup sliding mechanism. Special attention is paid to minimise the overall gripper size; its diameter being kept to 75 mm, which is that of the end link of the common UR5 robot. A prototype of the gripper is built and its versatility is demonstrated in a short accompanying video.